Medical Costs of Stroke Care Between Women With and Without Dysmenorrhea: A Population-Based Comparison - Lin, Ya-Wen; Sung, Fung-Chang; Lin, Ming-Hung; Muo, Chih-Hsin; Teng, Yu-Kuei; Kao, Chia-Hung; Tzeng, Ya-Ling (Frontiers in Public Health, 2021)
Objective: This study investigated medical care costs of stroke type between age matched cohorts with and without dysmenorrhea, using the National Health Insurance Research Database. Methods: All 66048 dysmenorrhea and 66048 age and index-year matched comparison women with aged 15-44 years were collected in 1997-2013. We assessed the incidence of stroke and stroke subtype in two cohorts, and compared the risk of stroke and stroke subtype between two cohorts. In stroke development women, the proportional distributions of stroke subtypes by age between the 2 cohorts was compared. The hospitalization rate among stroke subtype between two cohorts in stroke women was also estimate. Medical cost, length of stay, and the medical cost within 30-day after stroke was also compared between two cohorts. Results: The stroke risk in dysmenorrhea was greater than comparisons (HR = 1.26, 95% CI = 1.11-1.42). Proportionally, hemorrhagic stroke (HS) significantly decreased with age in both cohorts, whereas ischemic stroke (IS) significantly increased with age when both cohorts were combined. The dysmenorrhea cohort had a higher portion of transient cerebral ischemia (TIA) stroke than comparisons (31.3% vs. 24.2%, p = 0.01), and a lower risk of hospitalization for IS (OR = 0.48, 95% CI = 0.21-0.69). Among the four stroke subtypes, the cost of care for TIA was the least (157USD±254). Average cost for stroke care was not significantly different between women with or without dysmenorrhea. Conclusion: The hospitalization rate and medical costs of TIA are lower than other types. All the women should prevent and treat TIA early to avoid recurrence or progression to major stroke events, and to reduce medical expenses, regardless of whether they have dysmenorrhea.